Traditional use of wild edible plants in the communities adjacent Mabira Central Forest Reserve, Uganda - Nyakoojo, Clement; Tugume, Patience (Ethnobotany Research and Applications, 2020)
Background: Wild edible plants have been collected and consumed by humans since pre-historic times. They act as safety nets in times of food shortage and improve the livelihoods of rural communities. Evidence has proven that they contribute to nutritional health. However, dependence on wild edible plants is being threatened by loss of indigenous knowledge, environmental degradation, and limited scientific validation. Methods: This study focused on documentation of indigenous knowledge, identity of, and use of wild edible plants in 13 villages of Mabira Central Forest Reserve (CFR). Data were collected through structured and semi-structured interviews, field visits, and free listing. A literature review was carried out to obtain nutritional data on the identified plants. Results: The twenty-seven plant species identified were distributed in 24 genera and 22 families. The majority of wild edible plant species were trees (41%) while climbers (3%) were the least likely to be edible. Fruits (66%) were the major parts consumed while tubers and roots were the least (4%). Most fruits (74%) were consumed raw; in contrast all the vegetables were cooked. Aframomum angustifolium (Sonnerat) K. Schum was the predominant wild food consumed by 74% of the 57 households surveyed. Reviewed nutritional data showed that the identified plants possess a variety of minerals and antioxidants that improve human health and nutrition. Conclusion: Wild edible plants play a significant role in the nutritional health of consumers. Therefore, research on priority plants for domestication, value addition and standardization into food supplements is recommended. Results on such aspects might motivate local communities to conserve forest biodiversity through sustainable use and management of wild edible plants. Key words: Indigenous knowledge; livelihoods; nutritive value; Mabira Forest Reserve; wild edible plants.